Psychometric Evaluation of the Brief Acculturation Scale for Hispanics - Mills, Sarah D. (2014)
This study examined the psychometric properties of the Brief Acculturation Scale for Hispanics (BASH), a four-item, language-based measure of acculturation. Participants in the study were 435 Hispanic Americans from a large metropolitan area with English or Spanish language preference. Internal consistency reliability was strong in both language-preference groups. Multiple-group confirmatory factor analysis was used to evaluate the structural validity of the measure. A unidimensional factor structure was found for both English and Spanish language-preference groups and items loaded equivalently across groups, demonstrating measurement invariance. The BASH had good convergent validity and incremental validity. Overall, this study provides further evidence that the BASH offers a brief, reliable, and valid measure of acculturation to be used among Hispanic Americans.